Internationalising higher education - experience of some Asian countries and lessons for Vietnam - Lê Thị Thu Trang (Tạp chí Nghiên cứu Khoa học Công đoàn, 2022)
Internationalising higher education is considered an inevitable development trend of national education, especially in the context of globalization and international integration deepening in all fields. Internationalising higher education offers a global learning experience, contributing to improving the quality of education and create a generation of international citizens. Valuable lessons for Vietnam in the process of internationalising higher education are experiences from countries with developed higher education in Asia.